Factors affecting taxpayer compliance at KPP Pratama Medan East in the time of the covid-19 endemic - Irna Triannur Lubis; Jenni Zain; Selvi Aristantya (Trigin Publisher, 2023)
This research aims to analyze the influence of Taxpayer knowledge and sanctions on Taxpayer Compliance at KPP Pratama Medan Timur during the Covid-19 Endemic. This type of research is causality research. The analytical method for this research is quantitative research. This research design uses a cross sectional design method with a sampling technique using purposive sampling. This research uses data analysis with the Partial Least Square (PLS) approach. The sampling method in this research was people the researcher met randomly and the sample was determined using the Slovin Formula, totaling 100 Taxpayers. Primary data collection techniques used questionnaires and interviews. The results of this study found that taxpayer knowledge has a significant effect on taxpayer compliance. This can be seen from the significance value of 0.000 below 5% (0.05), and the T-Statistics value of 4.976 exceeding the T-table (1.92). Meanwhile, sanctions did not have a significant effect on taxpayer compliance at the East Medan Pratama KPP during the Covid-19 Endemic. It showed a significant value of 0.844 above 0.05 and a T-statistic value of 0.197 which was smaller than the T-table of 1.92.